The Aesthetics of Digital Art Animation For Children In Social Media Programs (Journal of the College of Basic Education, 2025)
Digital art is described as any artwork created or displayed using digital technology as an integral part of the creative or performance process. It encompasses a wide range of techniques and methods, including digital graphics, animation, digital photography, video, digital sculpture, and interactive art, The aim of the research is to build a tool to measure the aesthetics of digital art in animated films, and to identify the aesthetics of the animated image of digital art directed at children in social media programs, for the years (2023-2024), The theoretical framework included the aesthetic concept of digital image, digital art, and social media programs. The chapter concluded with indicators and a presentation of previous studies. A deliberate sample of (2) animated films was chosen, according to an analysis tool, with conclusions and recommendations presented based on the results.